Gloves for Pesticide Applicators - Brett W. Bultemeier (EDIS)
The use of personal protective equipment (PPE) as directed by pesticide labels is an important part of compliance with pesticide use and for reducing the risk of exposure. The primary risk for exposure to pesticides is the hands and forearms, and chemical-resistant gloves are the primary way to reduce that risk. This publication discusses the type of gloves available, how to select which glove, how to clean and maintain them, as well as other important considerations to most effectively utilize this important piece of PPE.